Efeito da liraglutida sobre a fibrose hepática e células estreladas ativadas - Mesquita, Fernanda Cristina de (2017)
Liver fibrosis is the wound healing response to repeated injury of the liver. This process begins with the damage of the parenchymal cells and subsequent inflammation, characterized by the rupture of the hepatic architecture associated to the increase of the expression of the components of the extracellular matrix. The development of hepatic fibrosis is based on the activation of hepatic stellate cells (HSC) that undergo phenotypic changes and are characterized by loss of vitamin A deposition and increased cell proliferation, triggering hepatic microcirculatory dysfunction and fibrogenesis in patients with chronic liver disease (CLD). Liraglutide is a GLP-1 agonist (glucagon-like peptide 1) well established as an antidiabetic drug, but also has anti-inflammatory properties, in addition to the effectiveness for NAFLD (non-alcoholic fatty liver disease). Therefore, the aim of this study was to evaluate the effects of liraglutide on the HSC phenotype and liver microvascular function using diverse pre-clinical models of CLD. The results obtained demonstrate that Liraglutide de-activated human and rat HSC phenotype through a GLP1-Rindependent mechanism. Liraglutide did not affect the HSC viability but decreased cell proliferation. CLD-rats receiving liraglutide exhibited significantly lower portal pressure (-20%) with a consequent reduction in intrahepatic vascular resistance. There was also a marked improvements in hepatic vascular function, fibrosis, HSC phenotype and sinusoidal endothelial phenotype. The anti-fibrotic effects of liraglutide were confirmed in human liver tissue. In conclusion, this study demonstrates for the first time that liraglutide improves hepatic sinusoidal endothelium in clinically relevant experimental models of cirrhosis, which leads to improvement in fibrosis and portal hypertension, and therefore is valid in the treatment of advanced chronic liver disease.